Between the Cuban revolution and the “Chilean Way”: Intellectuals, culture and politics in the casa de las Américas and la quinta rueda pages - Schmiedecke, Natália Ayo [UNESP]; da Silva Júnior, José Antonio Ferreira (Universidad de Chile, 2021)
This paper discusses the two most revisited experiences of transition to socialism in the Latin American twentieth century: the Cuban Revolution and the Chilean Popular Unity government. To contrast Cuban and Chilean leftist conceptions of that period, we analyzed how the cultural magazines Casa de las Américas and La Quinta Rueda represented the agenda of the left. Based on these sources, we will discuss each government's cultural policies, the intellectual debates, the exchanges, and conflicts between the two revolutionary processes.
Entre la revolución Cubana y la “Vía chilena”: Intelectuales, cultura y política en las páginas de casa de las Américas y la quinta rueda
Keywords: Cuban Revolution; Cultural magazines; Intellectual History; Popular Unity